Cohesive Devices in the United Nations Arabic Texts and their English Translations: A Corpus-based Study - CHAALAL, Imen (Journal of Human Sciences, 2016)
This paper examines one essential aspect of equivalence in translation: textual cohesion. It aims to contrast Arabic and English cohesive devices in some United Nations texts, find out how they are interpreted as equivalents and examine the regularity in shifting cohesion. A parallel corpus of texts of 15 Arabic texts and their English translation counterparts are selected and the distribution of their cohesive devices is analysed. Using computer software, the use of cohesive devices is compared. Findings reveal that Arabic and English have more similarities than differences in terms of the cohesive devices used though there are obvious differences in the frequency of their occurrence. The similarities are significantly preserved for the purpose of accurateness, transparency and formality that characterise the language of legal texts.